Environmental drivers of wild orchid distribution: Soil properties shape habitat preferences in the Po Delta Regional Park (Italy) - Lisa Scramoncin; Renato Gerdol; Anna Cazzavillan; Fabio Vincenzi; Lisa Brancaleoni (PLoS ONE, 2026)
European terrestrial orchids inhabit a wide range of habitats, including forests, grasslands, wetlands and anthropogenic ecosystems. This study investigates the ecological preferences of seven wild orchid species in the Po Delta Regional Park (Northern Italy), focusing on how environmental gradients of soil properties such as moisture, salinity, pH, and nutrient availability shape species distribution and niche breadth. We conducted vegetation surveys and field measurements of soil variables across 27 sites. Species differentiation along environmental gradients was analysed through Multivariate Analysis of Variance (MANOVA), Principal Component Analysis (PCA), and Outlying Mean Index (OMI) analysis to assess niche breadth and marginality. We then compared normalized Ellenberg Indicator Values (EIVs) for Moisture, Reaction, Salinity, and Nutrients with measured soil variables [Volumetric Water Content, pH, salinity, ammonium (NH 4 + ), nitrate (NO 3 − ), and phosphate (PO 4 3− ) concentrations] using Linear regression. Moisture and salinity were key drivers of orchid distribution. Anacamptis laxiflora and Anacamptis palustris were associated with wet, saline environments, whereas Anacamptis pyramidalis and Anacamptis coriophora preferred drier, nutrient-poor soils. Anacamptis laxiflora exhibited highest marginality and narrowest niche breadth, indicating high specialization. In contrast, Ophrys apifera showed lowest marginality and highest tolerance, reflecting its generalist strategy and adaptability to a broad range of soil conditions. EIV-Moisture and EIV-Salinity showed strong correlations with field measurements, whereas EIV-Nutrients and EIV-Reaction were less predictive. These findings emphasize the importance of conserving environmental heterogeneity, especially in human-dominated ecosystems, to support both generalist and specialist orchid species.